A pilot randomised controlled trial to assess the feasibility and acceptability of recovery-focused therapy for older adults with bipolar disorder. Issue 6 (24th November 2022) - Tyler, Elizabeth; Lobban, Fiona; Sutton, Christopher; Hadarag, Bogdan; Johnson, Sheri; Depp, Colin; Duncan, Deborah; Jones, Steven H.
Abstract : Background: Despite increasing evidence for the effectiveness of individual psychological interventions for bipolar disorder, research on older adults is lacking. We report the first randomised controlled trial of psychological therapy designed specifically for older adults with bipolar disorder. Aims: To evaluate the feasibility and acceptability of recovery-focused therapy, designed in collaboration with older people living with bipolar disorder. Method: A parallel, two-armed, randomised controlled trial comparing treatment as usual with up to 14 sessions of recovery-focused therapy plus treatment as usual, for older adults with bipolar disorder. Results: Thirty-nine participants (67% female, mean age 67 years) were recruited over a 17-month period. Feasibility and acceptability of recruitment, retention (>80% observer-rated outcomes at both 24 and 48 weeks) and intervention processes were demonstrated. The majority of participants started therapy when offered, adhered to the intervention (68% attended all sessions and 89% attended six or more sessions) and reported positive benefits. Clinical assessment measures provide evidence of a signal for effectiveness on a range of outcomes including mood symptoms, time to relapse and functioning. No trial-related serious adverse events were identified. Conclusions: Recovery-focused therapy is feasible, acceptable and has the potential to improve a range of outcomes for people living with bipolar disorder in later life. A large-scale trial is warranted to provide a reliable estimate of its clinical and cost-effectiveness.